PENGARUH KEPEMILIKAN DENGAN KONEKSI POLITIK TERHADAP PERILAKU PENGHINDARAN PAJAK - Nur Awlia Az’ari; Anies Lastiati (KRISNA: Kumpulan Riset Akuntansi, 2022)
This study aims to examine whether company ownership, especially those represented by the board of commissioners and company shareholders who have political connections, has an effect on tax avoidance behavior. This study also examines whether the company's audit committee has a moderating impact on the influence between ownership structure and tax avoidance behavior. The results show that political connections have a positive effect on tax avoidance, meaning that the higher the political connection, the lower the CETR value, the higher the political connection in the company, the higher the tax avoidance. However, this study shows that the audit committee does not have a moderating impact on the relationship between these political connections and tax avoidance.